2019
DOI: 10.3390/ijerph16203951
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Exposure to Pesticides and Breast Cancer in a Region of Intensive Agribusiness Activity in Brazil: A Case-Control Study

Abstract: Background: Breast cancer is a serious public health problem and is the second most prevalent cancer type in the world. The purpose of this article is to evaluate the association between pesticide use and breast cancer in a region of intense agribusiness activity in the state of Mato Grosso, Brazil. Methods: A case-control study was conducted on women living in the city of Rondonópolis, in the south of Mato Grosso state. There were 85 cases of women with confirmed breast cancer and 266 controls who were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Our results are in accordance with results obtained in studies investigating genotoxicity in pesticideexposed populations of the region [24][25][26] as well as increased cancer risk in regions of agricultural use of pesticides [27]. The existing reports also indicate that genotoxic effects and increased cancer risk may not be specific to banana plantations, but can be anticipated in agriculture of various products with a high pesticide application.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are in accordance with results obtained in studies investigating genotoxicity in pesticideexposed populations of the region [24][25][26] as well as increased cancer risk in regions of agricultural use of pesticides [27]. The existing reports also indicate that genotoxic effects and increased cancer risk may not be specific to banana plantations, but can be anticipated in agriculture of various products with a high pesticide application.…”
Section: Discussionsupporting
confidence: 91%
“…Pesticides may pose a substantial risk for BC development. Current evidence is based, for instance, on case-control studies characterizing female environmental contact with organochlorines. Risk assessment studies about occasional pesticide exposure and BC development have also shown a positive association in multiple populations, with hazard risks reaching more than 4 times in some cases but not others. ,,,,,, This variability may result from various factors, such as epidemiological studies that analyze the overall population with individuals who are occasionally/accidentally exposed to pesticides versus target populations with high exposure, such as rural workers. The pesticide residues found in the present study were very similar to others identified in surveys of urine samples in populations worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Pesticides are toxic agrochemicals used for crop protection against insects, fungi, and pests. Their widespread use in various agricultural practices not only resulted in environmental contamination but also entailed a direct exposure to a population from a variety of sources, including residues in water, air, dust, and foodstuff, which represent routes of long-term exposures that have caused potential health problems, such as respiratory diseases, neurological dysfunctions, cancers, and reproductive disorders. …”
Section: Introductionmentioning
confidence: 99%